Pengembangan Modul Pembelajaran IPA Berbasis Etnosains Materi Interaksi Makhluk Hidup dengan Lingkungannya untuk Menanamkan Jiwa Konservasi Siswa Kelas VII SMP - Sari, Niken Purnama; Suhirman, Suhirman; Walid, Ahmad (BIO-EDU: Jurnal Pendidikan Biologi, 2020)
The purpose of this study is to develop ethnics-based science learning modules that have the feasibility to be used after validation. The research method uses the Borg & Gall development model which consists of 6 stages, namely a preliminary study stage, a research planning stage, a design development stage, a limited field test stage, a revised stage of the results of a limited field test stage, and a final product stage. This research is limited to the developing stage, namely the feasibility of the module. The instrument used was a questionnaire for module eligibility. The research subjects were 3 lecturers from Bengkulu State Islamic Institute which consisted of 1 language expert lecturer, 1 material expert lecturer, and 1 media expert lecturer. The results of the questionnaire analysis data by calculating the percentage of achievement in each component of the percentage of achievement of the eligibility criteria of the science learning module based on ethnoscience that was developed is suitable for use with a percentage of 92.00%, 76.25%, 86.25% (the category is very feasible, feasible, and very worthy). From the results of these data, it can be concluded that the module is feasible to be used as teaching material in supporting the teaching and learning process on the material interaction of living things with their environment in junior high school for class VII.